Il progetto Italant e la grammatica del corpus - Renzi, Lorenzo (Verbum – Analecta Neolatina, 2002)
In the first part of this paper, the author presents the main concepts of the ‘corpus grammar’ and he discusses it. He disagrees with the claim that the corpus grammar could compete with generative grammar and with other modern linguistic theories. The second part of the paper deals with the ‘Italant’ project, that aims to constitute a grammar of Old Italian (i.e. of the Old Florentin linguistic veriety, written between the middle of the 13th till 1300, approximatly). The author argues that such a grammar has to be made basically using the same criteria which lead the linguist when he tries to describe a living language, although this could sound paradoxical.